Effect of renal impairment on the pharmacokinetics of prucalopride: a single- dose open-label Phase I study - Smith WB; Mannaert E; Verhaeghe T; Kerstens R; Vandeplassche L; Van de Velde V (Dove Medical Press, 2012)
William B Smith,1 Erik Mannaert,2 Tom Verhaeghe,2 René Kerstens,3 Lieve Vandeplassche,3 Vera Van de Velde41Volunteer Research Group and New Orleans Center for Clinical Research, The University of Tennessee Medical Center, Knoxville, TN, USA; 2Janssen Research and Development, a division of Janssen Pharmaceutica NV, Beerse, Belgium; 3Shire-Movetis NV, Turnhout, Belgium; 4Independent Consultant Clinical Pharmacokinetics, Princeton, NJ, USAObjective: To evaluate the pharmacokinetics of prucalopride in individuals with renal impairment (RI).Methods: This open-label Phase I study (ClinicalTrials.gov identifier: NCT01674192) enrolled men and women aged 18–75 years who were classified by renal function: normal renal function (creatinine clearance ≥ 80 mL/min/1.73 m2), mild RI (50–79 mL/min/1.73 m2), moderate RI (25–49 mL/min/1.73 m2), and severe RI (≤24 mL/min/1.73 m2). All received a single oral dose of prucalopride 2 mg.Results: Thirty-four individuals (normal renal function: 10; mild RI: 8; moderate RI: 7; severe RI: 9) received prucalopride. In all groups, maximum plasma concentration was reached within 2–4 hours. There was no significant difference in exposure (area under the plasma concentration–time curve from time zero to infinity) between participants with mild RI and those with normal renal function. However, area under the plasma concentration–time curve from time zero to infinity values were 1.5- and 2.3-fold higher (P = 0.002 and P < 0.001) in patients with moderate RI and severe RI, respectively, than in those with normal renal function. The proportion of total body clearance accounted for by renal clearance was significantly reduced in those with RI.Conclusion: Clinically meaningful reductions in renal clearance were seen in participants with severe RI, which supports a decrease from the standard dose of prucalopride 2 mg daily to 1 mg daily in these individuals.Keywords: renal impairment, pharmacokinetics, prucalopride, safety